The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1073/pnas.2002486118
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological inhibition of PI5P4Kα/β disrupts cell energy metabolism and selectively kills p53-null tumor cells

Abstract: Most human cancer cells harbor loss-of-function mutations in the p53 tumor suppressor gene. Genetic experiments have shown that phosphatidylinositol 5-phosphate 4-kinase α and β (PI5P4Kα and PI5P4Kβ) are essential for the development of late-onset tumors in mice with germline p53 deletion, but the mechanism underlying this acquired dependence remains unclear. PI5P4K has been previously implicated in metabolic regulation. Here, we show that inhibition of PI5P4Kα/β kinase activity by a potent and selective small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 69 publications
3
26
0
Order By: Relevance
“…Most recently, a noncovalent dual PI5P4Ka/b inhibitor, CC260, was identified using a high-throughput screen among 5759 small molecules. CC260 treatment was shown to affect AKT phosphorylation and impair cellular energetics as demonstrated by changes in AMPK activation, mTOR inhibition, and decreased mitochondrial ATP production [60]. CC260 treatment increased the sensitivity of cancer cells to nutrient stress and was also able to selectively kill p53 mutant breast cancer cells [60], confirming several published data from our laboratory and others.…”
Section: Targeting Pi5p4ks With Small Molecule Inhibitorssupporting
confidence: 71%
See 1 more Smart Citation
“…Most recently, a noncovalent dual PI5P4Ka/b inhibitor, CC260, was identified using a high-throughput screen among 5759 small molecules. CC260 treatment was shown to affect AKT phosphorylation and impair cellular energetics as demonstrated by changes in AMPK activation, mTOR inhibition, and decreased mitochondrial ATP production [60]. CC260 treatment increased the sensitivity of cancer cells to nutrient stress and was also able to selectively kill p53 mutant breast cancer cells [60], confirming several published data from our laboratory and others.…”
Section: Targeting Pi5p4ks With Small Molecule Inhibitorssupporting
confidence: 71%
“…In fact, efforts have been made to identify and characterize pan inhibitors [33,34] as well as isoform specific inhibitors of PI5P4Ks [75,76], and over the years, there have been reports of more potent and selective small molecule inhibitors [60,[77][78][79], strengthening the evidence for efficient druggability of the PI5P4Ks. Recently in an attempt to identify drugs that are selectively lethal to cancer cells but not to normal cells, a novel compound, a131, was identified and interestingly, the group discovered that the target of the a131 compound is indeed the PI5P4Ks and it selectively regulated the cell cycle entry of Ras-activated cancer cells resulting in their death through mitotic catastrophe, while causing reversible growth arrest in normal cells [77].…”
Section: Targeting Pi5p4ks With Small Molecule Inhibitorsmentioning
confidence: 99%
“…All things considered, in the recent past, PI5P4Ks and their product PI-4,5-P 2 have risen from insignificance to being without a doubt one of the key metabolic sensors and regulators within the cell as well as pivotal players for interorganelle communication necessary for cell survival. With drugs being developed against these kinases (Davis et al, 2013;Clarke et al, 2015;Al-Ramahi et al, 2017;Kitagawa et al, 2017;Manz et al, 2020;Sivakumaren et al, 2020;Chen et al, 2021), targeting them in the near future in various diseases is looking brighter.…”
Section: Health and Disease: Pi5p4ks Emerge As Exciting Targetsmentioning
confidence: 99%
“…Due to the increasing interest on the role of PIP4K signalling in cancer, several inhibitors have been developed. We decided to exploit recently synthesized compounds named A-131 and THZ-P1_2 to understand if pharmacological inhibition of these lipid kinases could recapitulate the depletion of PIP4K2B by sh_RNAi (51, 52). We then treated hTERT_RPE1 cells for 24 hours with both these compounds, and we found that, as well as for the knock-down, inhibition of PIP4K led to decreased NE tension and chromatin decompaction (Figure 6A and 6B).…”
Section: Resultsmentioning
confidence: 99%
“…During the last years, the rising interest in these enzymes led to the synthesis of different inhibitors targeting this family of phosphotransferases. Here, we took advantage of two compounds, named A131 and THZ-P1_2 (51, 52), in order to understand if direct inhibition of the kinase activity of PIP4K could recapitulate the phenotypes appeared upon PIP4K2B silencing. Interestingly, both the compounds altered cell mechanics, finally impacting on cell capacity to migrate, similarly to cells depleted for PIP4K2B.…”
Section: Discussionmentioning
confidence: 99%